Pharmacokinetic interactions between 20(S)-ginsenoside Rh2 and the HIV protease inhibitor ritonavir in vitro and in vivo - Shi Jian; Cao Bei; Zha Wei-bin; Wu Xiao-lan; Liu Lin-sheng; Xiao Wen-jing; Gu Rong-rong; Sun Run-bin; Yu Xiao-yi; Zheng Tian; Li Meng-jie; Wang Xin-wen; et al. (Acta Pharmacologica Sinica, 2016)
Aim: 20(S)-Ginsenoside Rh2 (Rh2) has shown potent inhibition on P-glycoprotein (P-gp), while most HIV protease inhibitors are both substrates and inhibitors of P-gp and CYP3A4. The aim of this study was to investigate the potential pharmacokinetic interactions between Rh2 and the HIV protease inhibitor ritonavir. Methods: The effects of Rh2 on the cellular accumulation and transepithelial transport of ritonavir were studied in Caco-2 and MDCK-MDR1 cells. Male rats were administered Rh2 (25 or 60 mg/kg, po) or Rh2 (5 mg/kg, iv), followed by ritonavir (25 mg/kg, po). The P-gp inhibitors verapamil (20 mg/kg, po) or GF120918 (5 mg/kg, po) were used as positive controls. The concentrations of ritonavir in plasma, bile, urine, feces and tissue homogenates were analyzed using LC-MS. Results: Rh2 (10 μmol/L) significantly increased the accumulation and inhibited the efflux of ritonavir in Caco-2 and MDCK-MDR1 cells, as verapamil did. But Rh2 did not significantly alter ritonavir accumulation or transport in MDCK-WT cells. Intravenous Rh2 significantly increased the plasma exposure of ritonavir while reducing its excretion in the bile, and oral verapamil or GF120918 also increased plasma exposure of ritonavir but without changing its excretion in the bile. Interestingly, oral Rh2 at both doses did not significantly change the plasma profile of ritonavir. Moreover, oral Rh2 (25 mg/kg) significantly elevated the ritonavir concentration in the hepatic portal vein, and markedly increased its urinary excretion and tissue distribution, which might counteract the elevated absorption of ritonavir. Conclusion: Rh2 inhibits the efflux of ritonavir through P-gp in vitro. The effects of Rh2 on ritonavir exposure in vivo depend on the administration route of Rh2: intravenous, but not oral, administration of Rh2 significantly increased the plasma exposure of ritonavir.